2017
DOI: 10.1016/j.rbmo.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes in recipients are not associated with oocyte donor body mass index up to 28 kg/m 2 : a cohort study of 2722 cycles

Abstract: The effect of increasing donor body mass index (BMI) on clinical pregnancies was retrospectively analysed in a cohort of consecutive 2722 donor oocyte IVF cycles. The relationship between donor BMI and clinical pregnancies was assessed after adjusting for recipient BMI. Clinical pregnancy rates and live birth rates (LBR) were no different with increasing donor BMI (up to donor BMI ≤28 kg/m). The odds of pregnancy did not vary with donor BMI. Compared with donor BMI quartile 1, OR 95% CI of clinical pregnancy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In the present study, we do not consider that the total dose of Gn has significant statistical difference on blastocyst formation. A previous study showed that the dose of Gn had no relationship with the rate of embryo aneuploidy and clinical pregnancy outcome in a PGT cycle ( 38 ); these findings concur with our present results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we do not consider that the total dose of Gn has significant statistical difference on blastocyst formation. A previous study showed that the dose of Gn had no relationship with the rate of embryo aneuploidy and clinical pregnancy outcome in a PGT cycle ( 38 ); these findings concur with our present results.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, female BMI is not related to oocyte dysmorphism ( 37 ). In a cohort study of 2,722 cycles, researchers concluded that an oocyte donor BMI up to 28 kg/m 2 did not influence reproductive outcomes in recipients ( 38 ). A retrospective study of 6,500 IVF/ICSI cycles concluded that female obesity changed the uterine environment to impair IVF outcomes, although embryo quality was not affected ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using oocytes donation suggest that the adverse effect of increased BMI occurs at the level of oocyte and subsequent embryo [ 16 ]. Indeed, animal models have shown that obesity impairs the folliculogenesis, and thus results in a decreased oocyte/embryo development potential [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another recognized strategy to limit the influence of maternal age in implantation is oocyte donation. A 37-40% implantation rate (IR) has been reported in oocyte donation cycles, similar to the mean IR in IVF cycles [12][13][14][15].…”
Section: Introductionmentioning
confidence: 64%